Respon Pertumbuhan dan Produksi Senyawa Antioksidan pada Kalus Rosela (Hibiscus sabdariffa L.) dari Eksplan yang Berbeda secara in vitro - Noviati, Agustin; Nurchayati, Yulita; Setiari, Nintya (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2012)
Callus induction method can be used as tool in producing plant secondary metabolites. One of this compound found in roselle (Hibiscus sabdariffa L.) is antioxidant agent i.e ascorbic acid and carotenoid. The callus could be induced from any kind of explants in tissue culture. The aims of this experiment is to select explant which can encourage of callus formation beside high level of antioxidant compounds. The treatment of experiment was three kinds of explants i.e section of leaf, petiole and flower sepal. Sterilized explants were planted in MS (Murashige&Skoog) combined with 2 mg/L NAA dan 5 mg/L BAP. This experiment has been conducted by completly randomized design with 5 replicates Growth variable, included fresh weight callus, growth presentation, callus respons and biochemical variable like content of ascorbic acid and carotenoid were analyzed. The data were analyzed by analysis of varian and Duncan’s test at 95% significant level. Thed results showed that all kinds of explant dedifferentiated into callus which antioxidant content. Callus from leaf section had the higgest fresh weight with high level ascorbic acid. Whereas the higgest carotenoid level was obtained from callus-derived flower sepals. It conclused that in vitro callus was useful for producing plant biochemical compounds. Keywords : Callus induction, antioxidant agents, explants, ascorbic acid, cartenoid